Nilai Tarbiyah Ruhiyah dalam Novel Ranah 3 Warna dan Relevansinya Terhadap Pendidikan Karakter Islami - Sherly Unzilatil Kamilah; Imam syafi'I; Shobirin (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the values of tarbiyah ruhiyah (spiritual education) in Ahmad Fuadi's novel Ranah 3 Warna and to examine their relevance to Islamic character education. The research addresses the need to strengthen students' moral and spiritual dimensions amid contemporary character challenges by exploring literary works as an alternative educational medium. A qualitative approach with library research was employed. The primary data source is the novel Ranah 3 Warna, while secondary data were obtained from relevant books, journals, and previous studies. Data were collected through documentation techniques and analyzed using content analysis. The results reveal that the novel contains significant tarbiyah ruhiyah values, including prayer (doa), remembrance of God (dzikir), patience (sabar), trust in God (tawakal), sincerity (ikhlas), and self-reflection (muhasabah). These values are reflected through the main character's experiences, demonstrating resilience and spiritual maturity. Furthermore, the findings indicate that these values are highly relevant to Islamic character education, as they contribute to the development of religious awareness, emotional stability, self-control, and moral integrity. Thus, the novel can serve as an effective medium for integrating spiritual values into character education, particularly in fostering students' holistic development